2016
DOI: 10.1117/12.2218755
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the roles of standard rectifying circuits on the performance of a nonlinear piezoelectric energy harvester

Abstract: To enhance the energy conversion performance of piezoelectric vibration energy harvesters, such structures have been recently designed to leverage bandwidth-enhancing nonlinear dynamics. While key findings have been made, the majority of researchers have evaluated the opportunities when the harvesters are connected to pure resistive loads (AC interface). The alternating voltage generated by such energy harvesting systems cannot be directly utilized to power conventional electronics. Rectifying circuits are req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Similarly, Singh et al [12] concluded that nonlinear energy harvester contributed to larger vibration amplitude and frequency spectrum, compared with the linear system on SEH, SECE, and P-SSHI. Comparisons between SEH and purely resistive AC circuit were made in [13,14]. Results showed that SEH diminished power level and bandwidth due to the increased damping.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Singh et al [12] concluded that nonlinear energy harvester contributed to larger vibration amplitude and frequency spectrum, compared with the linear system on SEH, SECE, and P-SSHI. Comparisons between SEH and purely resistive AC circuit were made in [13,14]. Results showed that SEH diminished power level and bandwidth due to the increased damping.…”
Section: Introductionmentioning
confidence: 99%